Calf Performance Offspring of Cow Fed with Depolarizing Katuk Leaves - T. Amboro; A. Atabany; A. Suprayogi (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2023)
The birth and growth of dairy calves are important factors in the dairy cattle business. The growth of calves and mothers needs to be monitored in production management so that they can produce good seeds or milk according to the expected quality. This study aims to determine the effect of feeding depolarized katuk leaves on the performance of calves from cow consuming depolarized katuk. 21 gestation cows were three groups of seven cows each, the control group (feed complete),CF-DKPo (complete feed added with Depolarized Katuk Powder), CF-DKPe (complete feed added with Depolarized Katuk Pellets). As a feed addition, 100 grams of depolarized katuk feed were provided daily to each head which is given in the morning by mixing it with the morning feed. The treatment was served during at 10 days before calving day and up to 7 days birth. The research data consisted of gestational days data, daily gain data and calf body weight data from 0 – 90 days old. Data analysis on gestational age, body weight, and average daily gain of calf were by using one-way analysis of variance (ANOVA), and if there is a difference, continue with further testing (Dunnett’s test) using SPSS. The results showed that there were differences in birth weight and body weight in calves from mothers that were given depolarized katuk leaves. Calves from broodstock that consumed depolarized katuk leaves in pellet form had higher weights compared to the control and BKD treatments. Significant differences occurred in birth weight and calf ADG for each treatment. Katuk leaves that have been depolarized can be added to feed to help calves grow bigger.